Two-dimensional chromium phosphorus monolayer based gas sensors to detect NOx: A first-principles study - Zi-Han Yang; Jian-Hua Ren; Tao Huang; Wei-Qing Huang; Wang-Yu Hu; Gui-Fang Huang (Results in Physics, 2022)
The successive realization of two-dimensional (2D) material sensors to detect diverse gas molecules motivates us to take the first-principles calculations to investigate the adsorption of typical gases molecules (such as NO, NO2, NH3, SO2, H2O, CO2 and CO) on a 2D chromium phosphorus (CrP) monolayer. The adsorption energies are calculated after determining the optimum adsorption location and orientation of these molecules on the CrP monolayer surface. The results display that there is appropriate adsorption strength and obvious charge transfer between the 2D CrP monolayer and NOx (x = 1,2) molecules, indicating that the CrP monolayer is preferable adsorption ability towards NOx. The current–voltage (I-V) curves of the NOx-adsorbed CrP monolayer are further investigated by the nonequilibrium Green's function (NEGF) method. Before and after adsorption of NOx on the CrP monolayer, the transport characteristics show apparent response with a significant change of I-V curves, indicating that the CrP monolayer is a candidate material for high selectivity and sensitivity NOx sensor. These results demonstrate that the CrP monolayer has excellent sensing performance, close to or even better than other 2D materials like phosphorene and Ga-doped graphene, which makes it a potential gas sensor for NOx.